2016
DOI: 10.1088/1748-0221/11/12/p12021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neutral impurity concentration on charge drift mobility in p-type germanium

Abstract: We reported a new result of the neutral impurity scattering of holes that has impact on the charge drift mobility in high purity p-type germanium crystals at 77 Kelvin. The charge carrier concentration, mobility and resistivity are measured by Hall Effect system at 77 Kelvin. We investigated the contribution to the total charge drift mobility from ionized impurity scattering, lattice scattering, and neutral impurity scattering with the best theoretical models and experimental data. Several samples with measure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…We have reported that the neutral impurity scattering of holes has impact on the charge drift mobility in high purity p-type germanium at 77 Kelvin [1]. We have found that the total charge drift mobility in our p-type germanium crystals is dominated by both neutral impurity scattering and acoustic phonon scattering, and the neutral impurity concentration plays an important role on the charge drift mobility.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…We have reported that the neutral impurity scattering of holes has impact on the charge drift mobility in high purity p-type germanium at 77 Kelvin [1]. We have found that the total charge drift mobility in our p-type germanium crystals is dominated by both neutral impurity scattering and acoustic phonon scattering, and the neutral impurity concentration plays an important role on the charge drift mobility.…”
Section: Introductionmentioning
confidence: 61%
“…For the mobility caused by the scattering of optical phonons in germanium, µ O , it can be ignored for the same reason as we discussed in our previous work [1,24,25]. The mobility due to dislocation scattering, µ D can also be ignored since the dislocation density for n-type high purity germanium crystal is similar to that of p-type high purity germanium crystal [1,26,27].…”
Section: Other Scatteringsmentioning
confidence: 93%
See 2 more Smart Citations
“…Neither the drift model for electrons nor for holes takes into account the effects of crystal temperature or impurity concentrations on the charge-carrier drift velocities although these effects modify the drift velocities [34]. The effect of varying the hole-drift velocity was studied within the GRETINA [22] and AGATA collaborations [35].…”
Section: Charge-carrier Motion In High-purity Germanium Detectorsmentioning
confidence: 99%